2014
DOI: 10.1111/jora.12117
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sociopolitical Attitudes and Civic Education in the Civic Engagement of Black Youth

Abstract: Civic engagement is important for individual and community well-being. In the current study, we use survey data from a nationally representative sample to examine how sociopolitical attitudes, such as political cynicism, perceptions of institutional discrimination, and political efficacy, along with civic education relate to civic engagement among 593 Black youth, ages 15-25. We found perceived institutional discrimination, political efficacy, and civic education were associated with civic engagement, while po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
184
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(199 citation statements)
references
References 42 publications
15
184
0
Order By: Relevance
“…Using structural equation modeling, Flanagan et al (2007), found that African American, Arab American, Latina/o, and European American youth all had similar relationships between their perception of their school's democratic climate and level of civic commitment. Hope and Jagers (2014) found that exposure to civic education was related to African American youths' civic participation, a finding similar to those found in studies with predominantly White samples (Bachner, 2010;Campbell, 2008).…”
Section: Research On African American/latina/o Youth and Civic Engagesupporting
confidence: 81%
See 3 more Smart Citations
“…Using structural equation modeling, Flanagan et al (2007), found that African American, Arab American, Latina/o, and European American youth all had similar relationships between their perception of their school's democratic climate and level of civic commitment. Hope and Jagers (2014) found that exposure to civic education was related to African American youths' civic participation, a finding similar to those found in studies with predominantly White samples (Bachner, 2010;Campbell, 2008).…”
Section: Research On African American/latina/o Youth and Civic Engagesupporting
confidence: 81%
“…The findings from the study partially support the claims made by other researchers that pathways to civic engagement vary by racial/ethnic background and that models of civic engagements structured around White experiences may not be as applicable for youth of color (Ginwright & Cammarota, 2002;Hope & Jagers, 2014;Kirshner et al, 2003;Rubin, 2012;Shiller, 2013). For educators interested in promoting youth civic engagement among youth of color this suggests that schools should recognize students' different racial/ethnic identities when discussing civic participation.…”
Section: Implications For Policy and Practicesupporting
confidence: 78%
See 2 more Smart Citations
“…This has resulted in a paradigm shift from a deficit model to a strength-based model and growth of positive youth development. Researchers are exploring developmental assets among young people (e.g., Tolan, 2014;Hope & Jagers, 2014), as well as ethnic and racial adaptations of positive youth development approaches (e.g., Travis & Leech, 2014). In addition, research on varying forms of intervention, such as activity-based mentoring (Deane & Harré, 2014) and developmental-stage-specific intervention (Vuolo, Mortimer, & Staff, 2014) are charting pathways to more effectively implement research findings with young people.…”
Section: General Trends In Adolescent and Emerging Adulthood Researchmentioning
confidence: 99%